2020
DOI: 10.3390/insects11050312
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and Seasonality Affect Mosquito Community Composition in the West Region of Cameroon

Abstract: To identify potential sylvatic, urban and bridge-vectors that can be involved in current or future virus spillover from wild to more urbanised areas, entomological field surveys were conducted in rural, peri-urban and urban areas spanning the rainy and dry seasons in western Cameroon. A total of 2650 mosquitoes belonging to 37 species and eight genera were collected. Mosquito species richness was significantly influenced by the specific combination of the habitat type and the season. The highest species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 63 publications
3
53
0
1
Order By: Relevance
“…tritaeniorhynchus as the major vector of JE virus is typically rice field with short and sparse vegetation ( Erlanger et al, 2009 ; Keiser et al, 2005 ), although variations in breeding sites located into more urban areas have been reported possibly due to intense urbanization ( Liu et al, 2018 ). Modified land-use creates habitat fragmentation that might have played a role in the expansion of anthropophilic mosquitoes as well as forest-dwelling bats into residential areas, thus increasing the risk of human disease transmission ( Hassell et al, 2017 ; Mayi et al, 2020 ; Nunes et al, 2017 ). Current study results showed that 5 of 15 Cx.…”
Section: Discussionmentioning
confidence: 99%
“…tritaeniorhynchus as the major vector of JE virus is typically rice field with short and sparse vegetation ( Erlanger et al, 2009 ; Keiser et al, 2005 ), although variations in breeding sites located into more urban areas have been reported possibly due to intense urbanization ( Liu et al, 2018 ). Modified land-use creates habitat fragmentation that might have played a role in the expansion of anthropophilic mosquitoes as well as forest-dwelling bats into residential areas, thus increasing the risk of human disease transmission ( Hassell et al, 2017 ; Mayi et al, 2020 ; Nunes et al, 2017 ). Current study results showed that 5 of 15 Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters to determine each trap location in these habitats were similar to what is described by Mayi et al (2020) (32). We followed these criteria and the advice of Prof. dr. ir.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the spread of West Nile Virus [CDC (Centers for Disease Control and Prevention) (2019)], studies mainly focused on arboviruses (Savage et al, 2007;Farajollahi et al, 2011) while to our knowledge very few studies have investigated avian malaria in vectors (Kimura et al, 2010;Carlson et al, 2018). Something similar can be observed in Central Africa for example, where the main entomological studies have been based on anthropophilic mosquitoes and human malaria or other zoonotic diseases of medical importance (Kamgang et al, 2012;Mayi et al, 2020), while the role of mosquito species in the transmission of avian Plasmodium is practically unknown (Njabo et al, 2009(Njabo et al, , 2011. If researchers with different research interests but working in the same region or localities were willing to combine their sampling effort, material and data, it would be beneficial for everyone and likely add value to everybody's data.…”
Section: How Can We Determine the Vector Specificity Of Avian Plasmodmentioning
confidence: 94%